The Acquisition of Directionals in Two Mayan Languages - Pye, Clifton; Pfeiler, Barbara (Frontiers in Psychology, 2019)
We use the comparative method of language acquisition research to investigate children’s expression of directional expressions in two Eastern Mayan languages – K’iche’ and Mam. Both languages add clitics derived from verbs such as ‘go’ and ‘stay’ to their verb complex to express the direction an agent takes in the course of accomplishing an event. Historic changes to the prosodic structure of the verb complex in both languages explain why the directional clitics are predominately postverbal in K’iche’, while they occur in preverbal and postverbal positions in Mam. Prosody explains why K’iche’ children initially produce clitics postverbally, while Mam children produce clitics both preverbally and postverbally. Prosody also explains why the children acquiring both languages produce morphemes in the verb complex that are relatively infrequent but prosodically prominent, while omitting obligatory morphemes that are prosodically weak.